2018
DOI: 10.3390/ijerph15020292
|View full text |Cite
|
Sign up to set email alerts
|

Influential Effects of Intrinsic-Extrinsic Incentive Factors on Management Performance in New Energy Enterprises

Abstract: Background: New energy has become a key trend for global energy industry development. Talent plays a very critical role in the enhancement of new energy enterprise competitiveness. As a key component of talent, managers have been attracting more and more attention. The increase in job performance relies on, to a certain extent, incentive mechanism. Based on the Two-factor Theory, differences in influences and effects of different incentives on management performance have been checked in this paper from an empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
9
0
5
Order By: Relevance
“…The found results are consistent with the findings of Langfred and Rockman indicating that the empowerment induces in autonomy which improves indulgence in work improving satisfaction. Wang et al (2018) state that empowerment improves the employee psychological contact with the institute improving his institute perception and increasing his commitment to the institute.…”
Section: Discussionmentioning
confidence: 99%
“…The found results are consistent with the findings of Langfred and Rockman indicating that the empowerment induces in autonomy which improves indulgence in work improving satisfaction. Wang et al (2018) state that empowerment improves the employee psychological contact with the institute improving his institute perception and increasing his commitment to the institute.…”
Section: Discussionmentioning
confidence: 99%
“…High-polluting industries in China include thermal power, steel, metallurgy, building materials, mining and so on, and the contribution of high-polluting industries to China’s gross domestic product (GDP) is 36.1% in 2018 [4]. The local governments demand high-polluting industries to support the development of regional economies, but high-polluting industries can also threaten the ecological environment by pollution emissions [5]. As shown in Figure 1, the energy consumption of China’s high-polluting industries has been rising in recent years [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to working upon the identified factors in this study from the hospital administration's perspective, to manage the attitude of physicians toward EMR, a monetary incentive to the physicians having high utilization for EMR can be given, as in earlier studies, it was found that incentives are instrumental in changing the attitudes and behavior. [ 12 ] The monetary incentive can work as an extrinsic motivation for the adoption of EMR. [ 10 ] Moreover, in a previous study, it was also found that the monetary incentives can influence the physician's use of EMR.…”
Section: Discussionmentioning
confidence: 99%